Factors influencing Adoption of Knowledge Management Systems in India from a Micro, Small and Medium Enterprise’s Perspective - G.P., Girish; Joseph, Dennis; Roy, Souvik; Raju, G. Amar (International Review of Management and Marketing, 2015)
This study focuses on investigating factors which influence successful espousal of Knowledge Management Systems (KMS) in India from a Micro, Small and Medium Enterprise’s (MSME’s) viewpoint. MSME sector in India contributes about 7.5% of India’s GDP accounting for about 38% of the manufacturing output and 40% of the exports of the country. The study reviews MSME sector in India, literature pertaining to emergent Knowledge Management Systems and proposes a conceptual model having qualities of Technology Acceptance Model, Theory of Reasoned Action and Social Cognitive Theory. The prelude findings of the study based on literature aids us in laying out factors influencing successful espousal of KMS in a developing country like India from a MSME’s viewpoint. Empirical inquiry of the developed model in future would have practical implication and will facilitate MSMEs (which are major contributors to improvement of the economy) in successful espousal of Knowledge Management Systems and garner the latent benefits. Keywords: Micro, Small and Medium Enterprises, India, Knowledge Management Systems, Technology Acceptance Model, Theory of Reasoned Action, Social Cognitive Theory JEL Classifications: D80, D82, L21, L22, L25, O30